Excitonic insulator candidate Ta2NiSe5 and related transition-metal compounds studied by resonant inelastic x-ray scattering - Takashi Mizokawa; Claude Monney (Frontiers in Electronic Materials)
Resonant inelastic x-ray scattering (RIXS) can probe electron-hole excitations in excitonic insulators (EIs) which are realized by Coulomb attractive interaction between electrons and holes in semimetals or narrow gap semiconductors. In the present article, we review the exotic electronic state of an EI candidate Ta2NiSe5 which is probed by Ni 2p-3d RIXS as well as Ni 2p x-ray photoemission/absorption spectroscopy. The RIXS results on the exotic electronic state under the electron-hole and electron-lattice correlations suggest requirement of a new theoretical scheme which can describe itinerant electron-hole excitations and the localized charge-transfer excitations as well as the electron-lattice interaction.